2004
DOI: 10.1128/iai.72.12.7183-7189.2004
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Fibroblasts Infected with Salmonella enterica Serovar Typhimurium Mediate Osteoclast Differentiation and Activation

Abstract: The mechanisms whereby arthritogenic organisms may induce cartilage and bone erosions in infectiontriggered arthritis remain unknown. In this study, we asked whether an arthritogenic organism could contribute to osteoclast differentiation and activation through regulation of the receptor activator of NF-B ligand (RANKL) in synovial fibroblasts. Rat synovial fibroblasts were infected in vitro with Salmonella enterica serovar Typhimurium and monitored over time. The expression of RANKL in resting and infected sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…These findings are compatible with a previous report that describes prolonged culture of synovial fibroblasts after ST infection [54]. These findings suggest that while ST may invade into stromal-type cells without causing significant cell death, invasion does elicit marked and distinct cellular responses.…”
Section: Discussionsupporting
confidence: 82%
“…These findings are compatible with a previous report that describes prolonged culture of synovial fibroblasts after ST infection [54]. These findings suggest that while ST may invade into stromal-type cells without causing significant cell death, invasion does elicit marked and distinct cellular responses.…”
Section: Discussionsupporting
confidence: 82%
“…Upon LPS injection or Salmonella oral infection, we observed that serum RANKL levels were down-regulated within 5 h, while serum OPG levels were up-regulated over 24 h. Down-regulation of RANKL in response to LPS or infection was unexpected, because bacterial infection increases RANKL expression at both the mRNA and protein level in osteoblasts and synovial fibroblasts (33,34). Therefore, down-regulation of serum RANKL could require posttranslational regulation, such as suppression of RANKL shedding (35,36).…”
Section: Discussionmentioning
confidence: 91%
“…RANKL expressed on the surface of osteoblasts and stromal cells or soluble recombinant RANKL, supports osteoclast differentiation and activates mature osteoclasts to resorb bone in vitro (Lacey et al, 1998;Yasuda et al, 1998;Shin et al, 2003). Recently, several groups examined that bacteria or bacterial components induce the expression of RANKL from gingival fibroblasts, periodontal ligament cells, and synovial fibroblasts (Tiranathanagul et al, 2004;Zhang et al, 2004;Belibasakis et al, 2005). Monocytes and macrophages can differentiate into osteoclasts under a suitable condition prepared in vitro (Udagawa et al, 1990;Shin et al, 1995;Yasuda et al, 1998).…”
Section: Introductionmentioning
confidence: 99%